Tony Newstead (1923-2017) - Newstead, Mark; Pratt, Clemens; Burke, John; Gerrand, Peter (Journal of Telecommunications and the Digital Economy, 2017)
Tony Newstead, who died on 6 November 2017, was a pioneering figure in Australian and worldwide telecommunications network planning, as well as in Australian trad jazz as both a trumpeter and early bandleader. This obituary attempts to do justice to his career in both fields. In an Attachment, Dr Clemens Pratt provides a short memoir in appreciation of Tony’s role as his career mentor and colleague, and John Burke provides an appreciation of Tony’s innovatory role in pioneering open planning in Australian telecommunications.